EFFECT OF PESTICIDE ADDITION SEQUENCE ON THE PREPARATION OF PHYTOSANITARY SPRAY SOLUTIONS - Ramos, M. F. T. [UNESP] (2019)
The addition of adjuvants to herbicide solutions is aimed at preserving or enhancing the biological effect of treatment. However, it is commonly performed without knowledge of the physicochemical interactions between products. This study aimed to assess the effects of different addition sequences of the herbicide aminopyralid + fluroxypyr and adjuvants in the preparation of phytosanitary spray solutions on the surface tension and contact angle. Two experiments were carried out with herbicide doses of 1 and 2 L ha(-1) associated with the adjuvants mineral oil (MO), silicone-polyether copolymer (S1L), and a mixture of phosphatidylcholine (lectin) and propionic acid (LEC), all at a proportion of 0.3% v v(-1). The application rate was 150 L ha(-1). Surface tension was measured by the pendant droplet method. Contact angle was measured on the adaxial and abaxial surfaces of leaves of the pasture weed Senna obtusifolia and parafilm. Preparation sequence did not change the contact angle on any of the analyzed surfaces at a dose of 1 L ha(-1) of herbicide. For the dose of 2 L ha(-1), the adjuvants SIL and LEC showed a higher spreading when previously added to the herbicide. MO resulted in a higher spreading when added after the herbicide, with higher surface coverage. Therefore, the preparation sequence influences the dispersion of phytosanitary spray solutions on targets.